Three‐dimensional bioprinting human cardiac tissue chips of using a painting needle method. Issue 11 (1st August 2019) - Chikae, Shohei; Kubota, Akifumi; Nakamura, Haruka; Oda, Atsushi; Yamanaka, Akihiro; Akagi, Takami; Akashi, Mitsuru
Abstract: Three‐dimensional (3D) printers are attracting attention as a method for arranging and building cells in three dimensions. Bioprinting technology has potential in tissue engineering for the fabrication of scaffolds, cells, and tissues. However, these various printing technologies have limitations with respect to print resolution and due to the characteristics of bioink such as viscosity. We report a method for constructing of 3D tissues with a "microscopic painting device using a painting needle method" that, when used with the layer‐by‐layer (LbL) cell coating technique, replaces conventional methods. This method is a technique of attaching the high viscosity bioink to the painting needle tip and arranging it on a substrate, and can construct 3D tissues without damage to cells. Cell viability is the same before and after painting. We used this biofabrication device to construct 3D cardiac tissue (LbL‐3D Heart) using human‐induced pluripotent stem cell–derived cardiomyocytes. The constructed LbL‐3D Heart chips had multiple layers with a thickness of 60 µm, a diameter of 1.1 mm, and showed synchronous beating (50–60 beats per min). The aforementioned device and method of 3D tissue construction can be applied to various kinds of tissue models and would be a useful tool for pharmaceutical applications. Abstract : Bioprinting technology has potential in tissue engineering for the fabrication of scaffolds, cells, and tissues. However, these various printing technologies have limitation with respect to print resolution and due to the characteristics of bioink such as viscosity. The authors report a method for constructing of 3D tissues with a "microscopic painting device using a painting needle method" that, when used with the Layer‐by‐Layer (LbL) cell coating technique, replaces conventional methods.